Friction stir welding of hypereutectic Al-Si alloy: Analysis of microstructure, mechanical and wear properties - Kumar H.; Prasad R.; Kumar P.; Reddy N. (My University, 2025)
Recently developed technique, friction stir welding (FSW) is capable to counter the issues like porosity and slag inclusion developed during fusion-based welding of hypereutectic aluminium silicon alloy (Al-Si). Studies based on FSW of aluminium silicon alloy have been reported but there is no report on hypereutectic particularly. Hence, present study was taken in to consideration to investigate the feasibility of FSW for welding of hypereutectic aluminium silicon alloy. The results revealed FSW caused breakage of α-Al dendrites, refinement and re-distribution of acicular Si-particles due to stirring at high strain rate during welding. Hardness and wear improved substantially of welded alloy with respect to its un-welded counterpart. The enhancement in microhardness and wear properties may be ascribed to breakage of α-aluminium dendrites, refinement and re-distribution of acicular silicon particles that led to hindered motion of dislocations and hence higher hardness and wear resistance. © 2023 Author(s).